Pengaruh Financing to Debt Ratio, Inflasi dan BI Rate terhadap Return On Asset BPRS Se-Karesidenan Madiun - Mursyidi, Matin; Febrilyantri, Candra (Masoem University, 2025)
A bank's ability to increase its profitability can indicate that its financial performance is improving. This ability can be seen through the Return on Assets (ROA). The higher a bank’s ROA, the greater its level of profitability. However, in reality, there are several discrepancies that affect ROA in this study. For example, when the Financing to Deposit Ratio (FDR) increases, ROA decreases; when inflation rises, ROA instead increases; and when the BI Rate goes up, ROA also increases. The purpose of this study is to examine the effect of FDR, inflation, and the BI Rate on the ROA of Islamic Rural Banks (BPR Syariah) in the Madiun Residency Region during the period of 2020 to June 2024. This study uses a quantitative approach with secondary data. The results show that FDR has a significant effect on ROA, inflation has a significant effect on ROA, and the BI Rate also has a significant effect on ROA. Simultaneously, FDR, inflation, and the BI Rate have a significant effect on ROA, with a coefficient of determination (R²) of 0.889006. This indicates that FDR, inflation, and the BI Rate collectively influence ROA by 88.90%, while the remaining 11.10% is influenced by other variables outside the model used in this study